Exploring light extraction efficiency of InGaN LED by creating structured voids in substrate with a femtosecond laser. (February 2017) - Wu, Shih-jeh; Tseng, Chun-Lung; Lu, Tsung-Sheng; Chen, Ying-Chieh; Tseng, Pei-Hsiang
Abstract: The applications of laser in processing of light-emitting diodes (LEDs) have become popular and inevitable. In this paper, we reported a complete fabrication process of InGaN LED involving a small modification of substrate by ultrafast laser. We created structured voids within the pattern sapphire substrate (PSS) with distributed Bragg reflector (DBR) on the backside by a tightly focused femtosecond laser. One or two passes of voids were aligned in rectangular grid shape and a study of different grid spacing was conducted. The wafers were stealth-diced by the same laser and mechanically cleaved after the on-wafer light output powers (LOP) are measured at 120 mA nominal current. The splitted chips are then undergone complete packaging process and LOP is measured again along with the electrical and irradiation properties. A raise of 1.35% of average on-wafer LOP is achieved at the optimal condition: 0.2 W total laser power for two passes of voids (grid spacing 40 µm) at focal depths set at 32 µm and 64 µm respectively from the backside. Also, the illumination efficiency is further improved by 4.59% after epoxy molding compound (EMC) packaging. The voids serve successfully as scattering or diffractive sources to reverse the stray photons in useful directions. Apart from the enhancement from both PSS and DBR there is still room for light extraction efficiency (LEE) improvement. The L-I-V relationship and diffusion angle are also presented. Highlights: Fs-laser creates voids in unit μm size with least impact on substrate integrity. Structured voids still improve the LEE of InGaN LED despite the PSS and DBR. Proposed method is compatible to and can be easily merged into production process. The dual-focusing optical design also helps to speed up the process.